On proper applications of Galërkin’s approach in structural mechanics courses - Ruta, G; Elishakoff, I (International journal of mechanical engineering education, 2022)
An incautious use of the well-known Galërkin’s technique to find approximate solutions of a differential problem may lead to apparently wrong results. Examples are based on an inverse approach to investigate buckling of compressed axisymmetric circular plates, a subject that is common in courses on mechanics of structures and stability of structural elements. We discuss how the mistake may originate and show how it is possible to recover the expected results, thus providing a means for the students to cross-check their outputs.